Participatory planning of appropriate rainwater harvesting and management techniques in the central rift valley dry lands of Ethiopia - Biazin, B.; Sterk, G.; Temesgen, M. (Canadian Center of Science and Education, 2014)
Despite the extensive efforts of rainwater harvesting and management (RWHM) interventions for moisture-stressed areas in Ethiopia, the adoption and wider dissemination of the newly introduced techniques have been generally meager. The objective of this study was, therefore, to develop appropriate RWHM techniques through a participatory planning process in the Central Rift Valley (CRV) dry lands of Ethiopia. To achieve this objective, a combination of literature reviews, focus group discussions, questionnaire surveys, agro-meteorological analyses and field experimentations were undertaken. Perceived agro-meteorological challenges were determined through the questionnaire survey and validated through meteorological data analyses. Potential in situ RWHM techniques were selected in a participatory process and field-tested for two consecutive growing seasons to evaluate their performances. Those techniques which were selected in a participatory process showed statistically higher crop yields than the existing practices under both low and normal rainfall years. The result of this study implied that the introduction of new RWHM techniques can be successful when they are adjusted and modified in accordance with the existing tillage, hoeing and related land management practices. It was concluded that participatory planning of in situ RWHM techniques allows both the utilization of existing knowledge and opportunities while empowering the farmers to select and introduce new practices as per the existing socioeconomic and environmental settings. The new participatory planning approach will augment the recent efforts of promoting various types of RWHM techniques for improved rainfed agriculture in the vast dry lands of Ethiopia.